A corpus-based study on a man is a lion in Mandarin Chinese and British English - Lixia, Wei (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
Previous studies seldom adopted the corpus as data source to conduct animal research on individual animals. Therefore, based on the GREAT AIN METAPHOR and the categorization of metaphors in terms of its nature, this study focused on the lion metaphors when the target domain is the man.The data for Mandarin Chinese? were collected from the Modern Chinese Corpus comp iled by the Centre for Chinese Linguistics of Peking University (CCL Corpus)The data for British English were collected from the British National Corpus (BNC ). This paper aims to identify the differences between the lion metaphor A MAN IS A LION in the two languages – Mandarin Chinese and British English. Through analyzing the 899 and 694 expressions that are mapped from the lion onto the man in Chinese and English respectively, the study has found supp ortive evidence for HUMAN BEINGS ARE ANIMALS by generalizing 14 lion metaphors under the umbrella of A MAN IS A LION in each language.